Reconstruction of Satellite Remote Sensing Images using Multifractal Analysis - Venkateswarlu, E; Sneha, Ch; Nair, Thara; Swamy, GP; M Bothale, Vinod (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 6 No 3&4 (2019): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
Remote Sensing Satellites are imaging the earth and providing different types of imagery in terms of volume, variety, velocity and variability. The spatial resolution is an important quality parameter and critical bottleneck in various remote sensing applications. In this work, we used multi-fractal based reconstruction to increase the spatial resolution of the remote sensing image. In multifractal analysis, image is treated as a nontrivial combination of a number of fractals. Multifractal characteristics of the low resolution image are extracted to compute the information transfer function and noise parameters. We generated an enhanced resolution image using low resolution image by a fractal based denoising and downscaling method. The reconstructed super resolution image is validated with original high resolution image through quality parameters like correlation coefficient and Structural Similarity Index (SSIM). How to cite this article: Sneha C, Venkateswarlu E, Nair T. Reconstruction of Satellite Remote Sensing Images using Multifractal Analysis. J Adv Res Geo Sci Rem Sens 2019; 6(3&4): 36-38.